1998
DOI: 10.1136/jcp.51.7.545
|View full text |Cite
|
Sign up to set email alerts
|

Secretory breast carcinoma in a 66 year old man.

Abstract: A secretory carcinoma of the breast, associated with axillary node metastasis, unilateral gynaecomastia, and chronic active hepatitis, occurred in a 66 year old man. Although secretory carcinoma of the breast usually occurs in children and adult women, our case shows that it can rarely occur in the elderly male. (J Clin Pathol 1998;51:545-547) Keywords: breast; secretory carcinoma; gynaecomastia Secretory carcinoma of the breast is a rare neoplasm first described in children and called "juvenile carcinoma."… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A total of 27 cases (including 2 cases from our study, see Table 3) of male patients with secretory breast carcinoma could be identified in the literature. 2,3,6,9,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Most affected patients were children and adolescents with a median age of 27 years. The tumors are usually located subareolarly.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 27 cases (including 2 cases from our study, see Table 3) of male patients with secretory breast carcinoma could be identified in the literature. 2,3,6,9,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Most affected patients were children and adolescents with a median age of 27 years. The tumors are usually located subareolarly.…”
Section: Discussionmentioning
confidence: 99%
“…Kuwabara et al [27] described a hormonal receptor-negative SBC in a man with gynecomasty due to chronic hepatitis C. Grabellus et al [35] related SBC (also negative for hormonal receptors) in a 46-year-old transsexual manto-woman who had undergone bilateral orchiectomy, penectomy, vaginoplasty, and mammaplasty augmentation, besides long-term cross-sex hormone treatment. Gynecomasty was present in six of the 26 cases described [12,14,21,24,27,33]. Despite its overall good prognosis, we believe that the most appropriate treatment for SBC appears to be surgical [1,2].…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, there have only been 25 previous reports of SBC in males [4,6,9,[12][13][14][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] of which seven reports of SBC were in boys of under 14 years old (Table 1). We report the first case in Brazil of this unusual tumor in a 13-year-old boy and its status after 10 years of follow up.…”
Section: Introductionmentioning
confidence: 90%
“…2 The youngest patient was a 6 year old boy 3 and oldest a 66 year old man. 4 We present a case of secretory carcinoma in a 19 year old man whose tumour cells were vimentin positive and oestrogen and progesterone receptor negative.…”
Section: Secretory Carcinoma Of the Male Breastmentioning
confidence: 98%